America's Captives : Treatment of POWs from the Revolutionary War to the War on Terror - Springer, Paul J. (Book collections on Project MUSE., 2010)
"Focusing on each major war in turn, Springer examines the lessons learned and forgotten by American military and political leaders regarding our nation's experience in dealing with foreign POWs. He highlights the indignities of the Civil War, the efforts of the United States and its World War I allies to devise an effective POW policy, the unequal treatment of Japanese prisoners compared with that of German and Italian prisoners during World War II, and the impact of the Geneva Convention on the handling of Korean and Vietnamese captives. In bringing his coverage up to the so-called War on Terror, he also marks the nation's clear departure from previous practice--American treatment of POWs, once deemed exemplary by the Red Cross after Operation Desert Storm, has become controversial throughout the world."--Jacket.